Assessment of accuracy of Cockcroft-Gault and MDRD formulae in critically ill Indian patients - Kharbanda, Mohit (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Cockroft-Gault (CG) and Modification of Diet in Renal Disease (MDRD) formulae have not been validated in critically ill Indian patients. We sought to quantify the discrepancy, if any, in Glomerular Filteration Rate (GFR) estimated by CG and MDRD formulae with 24 hrs urine Creatinine Clearance (Cr Cl). MATERIALS AND METHODS: Prospective cohort study in 50 adult patients in a mixed medical-surgical intensive care unit. Inclusion criteria: Intensive Therapy Unit (ITU) stay >48 hrs and indwelling urinary catheter. Exclusion criteria: Age <18 years, pregnancy, dialysis, urine output <400 ml/day and patients receiving ranitidine, cefoxitin, trimethoprim or diuretics. We estimated Creatinine Clearance by CG and MDRD formula and measured GFR by 24 hrs urine creatinine clearance. Bland Altman plot was used to find the difference between the paired observations. The association between the methods was measured by the product moment correlation coefficient. RESULT: The mean GFR as calculated by Creatinine Clearance was 79.76 ml/min/1.73 m(2) [95% Confidence Interval (CI) 65.79 to 93.72], that by CG formula was 90.05 ml/min/1.73 m(2) [95% CI: 74.50 to 105.60], by MDRD was 85.92 ml/min/1.73 m(2) [95% CI: 71.25 to 100.59]. The Bias and Precision between CG and Cr Cl were −4.5 and 140.24 respectively, between MDRD and Cr Cl was −6.1 and 122.52. The Correlation coefficient of CG formula as a measure of GFR was 0.65 (P < 0.0001), that of MDRD was 0.70 (P < 0.0001). CONCLUSION: We conclude that CG and MDRD formulae have a strong correlation with measured GFR but are not a reliable measure and overestimate GFR in critically ill Indian patients.